Representations of odor plume flux are accentuated deep within the moth brain - Baker Thomas C (Journal of Biology, 2009)
Abstract Odor space, the representation of odor quality in the insect brain, is known to be optimally resolved when lateral inhibitory pathways are functioning normally. A new study published in the Journal of Biology now shows that odor time resolution also depends on the normal functioning of such pathways.